Criss-cross Heart: A Complex Congenital Heart Disease (Journal of Armed Forces Medical College, Bangladesh, 2020)
A criss-cross heart is a rare congenital heart disease that is commonly associated with complex cardiac defect. Criss-cross heart is characterized by crossing of the inflow streams of the two ventricles, due to twisting of the heart during development. As a result the axis of the openings of the atrioventricular (AV) valves remain non parallel. We report a case of 2.5 months old baby with criss-cross spatial relationship of the atrioventricular valve with double outlet right ventricle with Pulmonary Artesia and atrial and ventricular septal defect. The diagnosis was confirmed by 2D and color Doppler Echocardiography in subxiphoid long-axis and coronal plane sweeps. Due to the complex structural changes and rarity of the anomaly, the diagnosis is often missed. In this case report we emphasized on diagnosis feature of presentation and surgical techniques required to correct or palliate the defects.Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 214-216